Investigation and Evaluation of Genetic Diversity of Plasmodium falciparum Kelch 13 Polymorphisms Imported From Southeast Asia and Africa in Southern China - Feng, Jun; Kong, Xiangli; Xu, Dongmei; Yan, He; Zhou, Hongning; Tu, Hong; Lin, Kangming (Frontiers in Public Health, 2019)
Objectives In this study, we aimed to analyse the genetic diversity of the Plasmodium falciparum Kelch 13 propeller allele mainly imported from Southeast Asia and Africa in southern China, including the provinces of Yunnan and Guangxi. Methods At enrolment, we collected blood samples from patients with confirmed cases of malaria infection between January 2012 and December 2017, for analysis. Individual patient information was obtained via a malaria surveillance system. The malaria infections and Kelch 13 mutations were diagnosed by using a nested PCR method. Results The K13 propeller genotype was identified in 283 P. falciparum cases from 18 counties in Yunnan and 22 counties in Guangxi. Forty-six isolates (46/283, 16.3%) harboured K13 mutant alleles were detectedin all isolates: 26.8% in Yunnan (33/123) and 8.1% in Guangxi (13/160). A total of 18 different K13 mutations were detected. Only the F446I mutation was detected in Yunnan isolates, and F446I was more frequent (20/46, 43.5%) than other alleles. Further, the temporal distribution of the F446I mutation ratio from 2012 to 2015 exhibited no significant difference in Yunnan Province (2012, 2/13, 15.4%; 2013, 7/40, 17.5%; 2014, 7/33, 21.2%; 2015, 4/37, 10.8%, p = 0.121). A578S allele was the main K13 mutation (5/283, 1.8%) from Africa. The K13 mutant allele was present in 33.3% of indigenous isolates, 27.4% of isolates from Southeast Asia, and 7.9% of isolates from Africa. The analysis of 10 neutral microsatellite loci of 60 isolates showed that at the TAA109 locus, the expected heterozygosity of F446I (He = 0.112 ± 0.007) was much lower than that of wild type and other mutation types in Myanmar isolates. With respect to geographic distribution, TAA109 also exhibited a significant difference between isolates from Southeast Asia (He = 0.139 ± 0.012) and those from Africa (He = 0.603 ± 0.044). Conclusions The present findings on the geographic diversity of K13 mutant alleles in P. falciparum may provide a basis for routine molecular surveillance and risk assessment, to monitor artemisinin resistance in China. Our results will be helpful for developing a genetic molecular marker to trace the malaria infection source during the elimination and post-elimination phases.